Influence of Resistance Training Proximity-to-Failure, Determined by Repetitions-in-Reserve, on Neuromuscular Fatigue in Resistance-Trained Males and Females - Martin C. Refalo; Eric R. Helms; D. Lee Hamilton; Jackson J. Fyfe (SpringerOpen, 2023)
Abstract Background This study examined the influence of proximity-to-failure in resistance training (RT), using subjective repetitions-in-reserve (RIR) prediction, on neuromuscular fatigue and perceptual responses. Methods Twenty-four resistance-trained males (n = 12) and females (n = 12) completed three experimental trials in a randomised order, each involving six RT sets (barbell bench press) with 75% 1-RM performed to either momentary muscular failure (FAIL), 1-RIR, or 3-RIR. Changes in lifting velocity with a fixed load were assessed from pre-exercise to post-exercise with the aim of quantifying acute neuromuscular fatigue (4 min post-exercise) and the associated time course of recovery (24 and 48 h post-exercise), and from the first to final set performed. Perceptual responses to RT were assessed at multiple time points during and following RT. Results Decreases in lifting velocity at 4 min post-exercise were greater for FAIL ( − 25%) versus 1-RIR ( − 13%) and 3-RIR ( − 8%), with greater decreases for male ( − 29%) versus female ( − 21%) participants following FAIL. At 24 h post-exercise, decreases in lifting velocity were greater for FAIL ( − 3%) and 1-RIR ( − 3%) versus 3-RIR (+ 2%), with all between-protocol differences diminishing at 48 h post-exercise. Loss of lifting velocity from the first to final set was greater for FAIL ( − 22%) versus 1-RIR ( − 9%) and 3-RIR ( − 6%), with a greater lifting velocity loss from the first to final set for males ( − 15%) versus females ( − 9%). As proximity-to-failure neared, ratings of perceived discomfort, exertion, and muscle soreness increased, general feelings worsened, and perceived recovery decreased. Conclusion These findings support a linear relationship between RT proximity-to-failure and both acute neuromuscular fatigue and negative perceptual responses, which may influence long-term physiological adaptations and adherence to RT.